Ecotourism development at Candi Gedong Songo: A contingent valuation method approach - Muhammad Adi Adrian; Sucihatiningsih Dian Wisika Prajanti; Saifudin Zuhri (Journal of Economics Research and Policy Studies, 2026)
Tourism provides both direct economic benefits and multiplier effects for other sectors of society. However, the management of Gedong Songo Temple, which focuses on increasing tourist numbers, tends to ignore the external impacts on the preservation of cultural heritage and the environment, necessitating a focus on sustainability principles. This study aims to determine the willingness to pay of tourists for the sustainable development of Gedong Songo Temple as a tourist attraction. Primary data was obtained based on interviews and questionnaires with 109 tourist respondents who visited Gedong Songo Temple. Respondents were selected using purposive sampling, and the analysis was conducted statistically using CVM. The results of this study show that according to the contingent valuation method, 98 of the 109 tourist respondents are willing to pay more for the development of the Gedong Songo Temple tourist attraction, with an average WTP value of IDR 28,000 per tourist and a total willingness to pay per year for the Gedong Songo Temple tourist attraction of IDR 7.9 billion. These results confirm that tourists appreciate conservation efforts, facility improvements, and increased comfort when visiting the Gedong Songo Temple tourist attraction.